Claustrophobia Virtual Reality Exposure Therapy – An Interactive Game for Reducing Anxiety in Closed Spaces - Marian MARALOI; Oana MITRUȚ; Alin MOLDOVEANU; Florica MOLDOVEANU (Communications of International Proceedings, 2020)
Virtual Reality Exposure Therapy (VRET) is becoming an increasingly popular mechanism for treating a wide range of psychological disorders, such as phobias. The concept behind this therapy is to transpose the patient into a virtual environment in which he is exposed to various factors that trigger the feeling of fear at different levels. Thus, he has the guarantee of not being endangered while adapting to the conditions of the virtual environment. In this way, efficient virtual reality systems are evoked to generate in time an emotional response that contributes to reaching a final result of the treatment. However, there are a wide range of problems that prevent the adoption of large-scale virtual reality systems, such as high development costs, the depth of research on several disorders is still limited and the difficulty for patients to fully understand their relationship with the virtual system and the outcome of the treatment. This project brings in a virtual environment that exposes the user to different gradual elements in terms of claustrophobia, consulting him/her at key moments in the game in order to obtain a more detailed analysis of the anxiety index evolution in time.
Keywords: Phobia; Claustrophobia; Virtual Reality; Game.